2013
DOI: 10.1074/jbc.m112.438275
|View full text |Cite
|
Sign up to set email alerts
|

A Shared Endoplasmic Reticulum-associated Degradation Pathway Involving the EDEM1 Protein for Glycosylated and Nonglycosylated Proteins

Abstract: Background: N-Glycan processing and interactions with lectins regulate the quality control and endoplasmic reticulumassociated degradation (ERAD) of glycoproteins. Results: Most of the same machinery targets nonglycosylated misfolded proteins. Conclusion: They share some membrane and luminal ERAD machinery but not all cytosolic components. Significance: ER glycan-interacting proteins must possess a dual specificity for glycan structure and for exposed misfolded polypeptide domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 53 publications
5
59
0
Order By: Relevance
“…S. cerevisiae lacks a true calnexin (145). Calnexin and calreticulin have been shown to compete with BiP for binding to specific glycoproteins (112), but calnexin also binds nonglycosylated substrates (146). This may explain why compromised Kar2/BiP function in yeast leads to a co-translational folding defect (evidenced by the appearance of different glycosylated species) that is not observed in mammalian cells (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…S. cerevisiae lacks a true calnexin (145). Calnexin and calreticulin have been shown to compete with BiP for binding to specific glycoproteins (112), but calnexin also binds nonglycosylated substrates (146). This may explain why compromised Kar2/BiP function in yeast leads to a co-translational folding defect (evidenced by the appearance of different glycosylated species) that is not observed in mammalian cells (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…This initial step induces additional mannose trimming to promote recognition of the misfolded N-glycoprotein by downstream ERAD machinery before removal from the ER and subsequent degradation (6,21,22). Despite this traditional view, recent evidence from multiple investigators has begun to reevaluate how N-linked glycan processing contributes to mammalian ERAD (11,(23)(24)(25)(26)(27)(28). In support of this growing debate, we recently reported that MAN1B1 resides in the Golgi complex in numerous human cell lines rather than in the ER (29).…”
mentioning
confidence: 86%
“…Intriguingly, it was concluded that EDEM3 possesses ␣1,2-mannosidase activity in addition to a KDEL sequence that endows it with the ability to traverse the ER and be retrieved from later compartments. It is noteworthy that EDEM1 and the downstream ERAD lectins XTP3-B and OS-9 were reported to interact with and enhance ERAD in a glycan-independent manner in mammalian cells (23,24,26,27). Several of these proteins are up-regulated during ERAD or the unfolded protein response, so if one or more of them are capable of initiating ERAD, this could have diminished the need for MAN1B1 mannosidase activity in promoting ERAD during subsequent evolutionary events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another ER component that has been proposed to act in the N-glycan-independent QC is EDEM1. It has an important role in accepting substrates from CNX and targeting them for degradation (2) but has recently been shown to be also capable of protein-protein interactions involving non-N-glycosylated misfolded proteins, targeting them to ERAD (50).…”
Section: Discussionmentioning
confidence: 99%